Manajemen Peningkatan Mutu Tenaga Pendidik Pada Sekolah Dasar Islam Terpadu Al-Farih Kabupaten Bima - Fiki Kusuma Weranata Putra; Narimah; Haerul (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
The purpose of this study was to find out: Management of educators and education staff at SDIT Al-Farih Bima Regency, obstacles in implementing the management of educators and education staff at SDIT Al-Farih Bima Regency, solutions in overcoming obstacles from problems regarding conflicts that occur between educators. This study uses a descriptive qualitative research method. The research was conducted at SDIT Al-Farih School, Bima District. The subject of this research is the principal at SDIT Al-Farih, Bima district. While the informants: are teachers and Administrative Personnel. Data collection techniques used are interviews and documentation. The technique used to check the validity of the data is triangulation with sources and methods collected in places and situations that are different from the data. Data analysis techniques using interactive methods include data collection, data reduction, presentation, and conclusion. The results of this study: The management of teaching staff at SDIT Al-Farih, Bima Regency includes recruitment, selection, placement, orientation, coaching and training, transfers, and dismissals. Coaching and training are the main focus in the management of educators. Coaching is carried out routinely and periodically with the aim of minimizing conflicts that may occur in the school environment. While training is tailored to the needs of teaching staff, with the aim of improving the quality of teaching staff. Obstacles in the implementation of teaching staff development in the form of the unavailability of adequate space, and non-innovative coaching routines lead to boredom, and the implementation of learning coaching outside the city for one month raises problems for female educators. The solution is 1) the foundation maintains good relations with teachers so that misunderstandings do not occur between teachers and the foundation and 2) minimize policies that are so strict that teachers feel comfortable in the work environment